Validation of the self-assessment of communication skills and professionalism for nurses - Thaís Josgrilberg Pereira; Ana Claudia Puggina
ABSTRACT Objectives: to translate, adapt cross-culturally and validate into Brazilian Portuguese the following instrument: "Self-assessment of communication skills and professionalism in residents" for the nursing professional, and to determine if personal characteristics and performance of the nurse interfere in the self-assessment about professionalism and interpersonal communication. Method: quantitative study. Results: the sample consisted of 110 nurses with mean age of 32 years old (± 7.3), most of them were women (n = 80; 72.7%). The internal consistency of the scale "Autoavaliação sobre profissionalismo e comunicação interpessoal entre enfermeiro e paciente" presented moderate and satisfactory reliability (α=0,712). Factorial analysis identified four factors: Interpersonal Skills, Exchange of Information, Honesty in the Relationship and Professionalism. Conclusion: the instrument is valid and reliable in Portuguese and for Brazilian culture. Interpersonal Skills changed with gender and marital status. Ability to exchange information was influenced by gender and working sector. Self-assessment of professionalism changed with marital status.